Perancangan Sistem Perpustakaan Berbasis Web - Supriyadi, Alam; Andryana, Septi; Gunaryati, Aris (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The research objective is to build a web-based library application. The research method consists of data collection, while the application implementation uses string matching, exact matching, and string matching algorithms. Entity-relationship diagrams are also used in building relationships in the database. Use cases are used as a description of the scope of a system that is built. The conclusion of this study is that; 1) This information facility system is very effective in influencing library admins to look for borrowed books, 2) Providing integration that produces non-digital information in one application, and 3) Librarians can take advantage of web-based automation and manage the circulation of book loans and book returns.